Harmonic Analysis with Symmetrical Space Phasor Components - König, Simon; Herold, Gerhard (2012 Electric Power Quality and Supply Reliability PQ2012, 2012)
The Symmetrical Space Phasor Components are a second transformation following the well-known transformation of the phase quantities into space phasor and zero sequence. With them it is possible to immediately indicate an occurring voltage or current unbalance in an electrical power network. Furthermore the unbalance can be assigned to a specific harmonic group. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.harmon
Keywords: Power quality; Power system harmonics